Organizational Commitment As A Mediation Between Organizational Culture, Extrinsic Motivation, And Democratic Leadership On Job Satisfaction At Dinas Lingkungan Hidup Dan Kehutanan Daerah Istimewa Yogyakarta - Rabit Pratama; Prayekti Prayekti; Kusuma Chandra Kirana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study is to explain organizational commitment as a mediation between organizational culture, extrinsic motivation, and democratic leadership on job satisfaction at the Dinas Lingkungan Hidup dan Kehutanan Daerah Istimewa Yogyakarta.. The population in this study amounted to 70 respondents. The sampling technique in this study was a census by taking the entire population of 70 respondents. The data collection used a questionnaire that was advertised to employees. This type of research uses quantitative methods and the use of primary data by involving the Smart PLS application. The analysis method focuses on descriptive analysis and inferential analysis consisting of Indicator Test, Model Fit Test, Hypothesis Test and Path Analysis. The results of this study prove that (1) Organizational culture influences organizational commitment (2) Extrinsic motivation influences organizational commitment (3) Democratic leadership influences organizational commitment (4) Organizational culture influences job satisfaction (5) Extrinsic motivation influences job satisfaction (6) Democratic leadership influences job satisfaction (7) Organizational commitment influences job satisfaction (8) Organizational commitment can be a mediating variable between the influence of organizational culture on job satisfaction (9) Organizational commitment can be a mediating variable between the influence of extrinsic motivation on job satisfaction (10) Organizational commitment can be a mediating variable between the influence of democratic leadership on job satisfaction.